Preparations of chemical sensors for simple formalin detection in contaminated food (A model for final project works for pre-service teachers in chemistry subject) - M. Adlim; . Hasan; Zarlaida Fitri; Yulida Amri; Martina Sari; Saiful Mahya (Syiah Kuala University, 2011)
Teaching chemistry must include some learning skills in scientific works. The students must have experience conducting small research in chemistry to train them the scientific methods. Some chemistry projects have been carried out by the students of teaching training college (FKIP) as called pre-service teachers in chemistry subject. The students were given research problem that is how to formulate a simple sensor for detection of formalin in contaminated food. The students were asked to review literature on the composition and analysis technique of formalin. The students wrote the research proposal and presented their proposal in front of four reviewers before they start conducting research. The project of formalin sensor preparation was started with studies of the active reagent composition in liquids phase, immobilizing the active reagent in soft media, and following with studies of the sensor sensitivity toward formalin contamination in food. The Schiff Fuchsine (SF) and NASH methods for aldehyde determination were chosen as the basic theory for formalin determination. Schiff Fuchsine (SF) in diluted sulfuric acid solution was kept overnight before use. The media for holding of the reagent was cotton coated with chitosan, then it was pasted in tacon foil, this sensor was called forpastrip (student project-1). It could detect formalin as low as 2% (v/v) of formalin or equivalent with 0,8% of formaldehyde in contaminated food and the expired date was 10 weeks. The forpastrips was tested on food and the chemical interference was also studied (student project-2). Another project was also carried by replacing the cotton with synthetic felt and this formula was recorded as student project-3. The SF reagent immobilized in synthetic felt coated by chitosan was inserted into narrow-plastic straws. The sensitivity of this sensor increased and the detection limit as low as 0.25% (v/v) of formalin in contaminated food and the expired date was more than 12 weeks. The forth project was replacing SF with NASH reagent immobilized in cotton coated by chitosan and inserted in narrow-plastic straws. The detection limit was 0.015% (v/v) of formalin in contaminated food. All Sensors were still effective to detect formalin in sample although the sample contained of sugar, salt, fat and protein as the impurity. The research findings were written by students in their final report (script, like a thesis) after approved by the two supervisors. They students then presented their research in comprehensive exam in front of reviewers before they were graduated. Having interviews with students, they claimed that they have experience in conducting research, have followed all scientific methods. They said the research theme is very interesting, simple, contextual and it might be applied in high schoo